Los problemas de liquidez en las microfinancieras, instituciones que fomentan el desarrollo productivo del territorio nacional - Nazareno Cevallos, Byron Alberto (2015)
The financiel analysis characterizes for being a fundamental tool because it analizes the operative behaviour ofa organization providing criteria for making managment decisions. The financial analysis in grounds on calculus of financial indicators of financial indicators wich measure the organiszations liquidity, managements to be in debt or solvency and profitability. The qualification job has like objective to determjine the liquidity plane and solvency of the business portfolio into the save and credit cooperative 16 de Junio, the liquidity indicator show the capacity to cover its obligations and the debt or solvency economic indicator measures the plane of participation of thind people. Finally, carried out the finalcial analysis that let to know that the cooperative shows a liquidity and solvency stable condition during the enalzed periods , wich let it mantain a stables tate of operations. Therefore; is recommended that the financial analysis be done at the end of each accounting period letting to ases the mode operations and proyecting for future events.